End-of-Life Decision-Making Capacity in Older People With Serious Mental Illness - Kotzé, Carla; Roos, Johannes Lodewikus; Ehlers, René (Frontiers in Psychiatry, 2021)
Background: The study’s main aim was to assess the end-of-life decision-making capacity and health-related values of older people with serious mental illness. Methods: A cross-sectional, observational study, was done at Weskoppies Psychiatric Hospital, Gauteng Province, South Africa that included 100 adults older than 60 years of age and diagnosed with serious mental illness. The Mini-Cog and a semi-structured clinical assessment of end-of-life decision-making capacity was done before a standardized interview, Assessment of Capacity to Consent to Treatment, was administered. This standardized instrument uses a hypothetical vignette to assess decision-making capacity and explores healthcare-related values. Results: The Assessment of Capacity to Consent to Treatment scores correlated (p<0.001) with the outcomes of the semi-structured decision-making capacity evaluation. Significant correlations with impaired decision-making capacity included: lower scores on the Mini-Cog (p<0.001); a duration of serious mental illness of 30-39 years (p=0025); having a diagnosis of schizophrenia spectrum disorders (p=0.0007); and being admitted involuntarily (p<0.0001). A main finding was that 65% of participants had decision-making capacity for end-of-life decisions, were able to express their values and engage in advance care discussions. Discussion & Conclusion: Healthcare providers have a duty to initiate advance care discussions, optimize decision-making capacity, and protect autonomous decision-making. Many older patients with serious mental illness can engage in end-of-life discussions and can make autonomous decisions about preferred end-of-life care. Chronological age or diagnostic categories should never be used as reasons for discrimination, and older people with serious mental illness should receive end-of-life care in keeping with their preferences and values.